Representações sociais, valores e atitudes face ao político em Angola e Moçambique - Heimer, Franz; Silva, Elisete Marques da; Ribeiro, Gabriel Mithá (Africana Studia, 2020)
This article presents selected results from a research project on the way the urban population in Angola “thinks” and” feels” about politics as they live it. The research, carried out from 2004 to 2004, in the framework of the Centro de Estudos Africanos – ISCTE (Lisbon), was carried aut by means of a sample-based survey and of numerous interviews - open as well as semistructured, with individuals as well as with groups. The most important part of the article is the basic political values held by the interviewees/respondents, and their perceptions with respect to the implementation of these values in their respective country, during the “I Republic” (following a “socialist” model) and the “II Republic” (declaredly democratic and “neo-liberal”). The data collected on this “subjective dimension” of politics fully confirms the critical analyses of the current political regimes in both countries.